The magnificent manifestation of Nd0.7Sr0.3MnO3 ceramics: A comprehensive exploration of different wet chemical routes via sol-gel and thermal treatment methods - Hon, Xiao Tong; Lau, Lik Nguong; Lim, Kean Pah; Awang Kechik, Mohd Mustafa; Chen, Soo Kien; Shabdin, Muhammad Kashfi; Miryala, Muralidhar; Shaari, Abdul Halim (Elsevier, 2024)
The mixed-valence manganite has sparked immense interest owing to its intriguing colossal magnetoresistance (CMR) effect. However, a research gap exists in the current literature regarding Nd-based manganites with intermediate bandwidth. This paper addresses this gap by investigating Nd0.7Sr0.3MnO3 (NSMO) ceramics prepared through two different synthesis approaches: the newly developed thermal treatment method (TT) and the well-established sol-gel method (SG). The XRD analysis revealed a single high-purity NSMO phase with insignificant alteration in Mn-O bond length and Mn-O-Mn bond angle for both samples. Nevertheless, SG exhibited larger particle size (209.3 nm) and better crystallinity in comparison to TT (178.6 nm). These factors significantly affect the magnetic transition width while preserving the Curie temperature, TC ≈ 246 K. Regarding electrical behaviour, TT showed a robust suppression of the metal-insulator transition temperature, TMI from 224 K (SG) to 182 K. This difference can be attributed to the existence of magnetic disordered layer at the grain boundaries. Consequently, this resulted in an increased scattering process and elevated resistivity from 8 Ω (SG) to 22 Ω (TT). Various theoretical models were employed to elucidate the transport mechanism at different temperature ranges. Interestingly, both samples displayed distinct magneto-transport behaviour despite negligible differences in their structural parameters. The occurrence of magnetoresistance peak in SG suggests a pronounced intrinsic CMR effect, while its absence in TT implies a dominant influence of extrinsic CMR. These findings highlight that the physical properties of the manganite are not only governed by their intragrain properties (TC) but are also influenced by intergrain contributions (TMI) when various synthesis routes were utilised. © 2024 Elsevier B.V.